Political Crisis in France: «Gilets Jaunes» and the End of the «First Period» of the Emmanuel Macron’s Governance - E. O. Obichkina (Vestnik MGIMO-Universiteta)
The article analyzes the current political crisis in France, the most striking manifestation of which is the «gilets jaunes» (yellow vests) movement. The current crisis is partly a consequence of the protracted identity crisis at both extremes of French political spectrum, resulting from a long period of relatively conflict-free alternation of left and center-right parties in a relatively favorable economic environment that accompanies the development of a consumer society and a social state. This model, which can be called «consumer democracy», has failed with the onset of the global economic crisis. The «stepsons» of modern capitalism, who are used to relying on social guarantees from the «welfare state» persistently reject the neoliberal recipes favorable among elites for dealing with the crisis. A wave of «gilets jaunes» protests seems to be contingent on the specific situation that emerged in France during the presidential elections of 2017 and the beginning of the era of Emmanuel Macron, who aims at restructuring French society and economy. Its main feature is the growing public disbelieve in and simultaneous collapse of both political parties that occupy and divide the French political Olympus at the time of power transition. Macron’s supporters enjoy an absolute majority in the Parliament without any meaningful opposition capable of opposing the president. It allows for a rapid rate of reforms but produces a backlash from society that perceives the situation as a violation of the dialogue between voters and legislators. Dissatisfied people without any hope to be heard join the ranks of the mass spontaneous movement of «gilets jaunes», triggered by the introduction of the so-called «environmental» tax. This movement can be viewed from different perspectives – political analysis can be complemented by historical anthropology, because the spontaneous nature of the protest resembles the anti-tax uprisings of the 17th-18th centuries. From a philosophical point of view, it seems to be a reaction of outsiders to deep social transformations associated with the pauperization of the middle classes, globalization, waves of migration and the digital revolution. The government’s response – revocation of the law that triggered the movement and the launch of «big national debates» – led to a relative decline in the activity of «gilets jaunes», but the main reason for the downturn is preparation for the upcoming European elections, which could be used as an opportunity to voice their discontent with the president and to return the civil protest in the electoral channel. The «gilets jaunes» movement hardly has any political future, but its experience, social potential and methods can be used in future protests, since its main agenda has not been exhausted – reconciliation of the neoliberal economic policies with the interests of the disadvantaged part of French society.